2002
DOI: 10.1289/ehp.02110917
|View full text |Cite
|
Sign up to set email alerts
|

Combining xenoestrogens at levels below individual no-observed-effect concentrations dramatically enhances steroid hormone action.

Abstract: The low potency of many man-made estrogenic chemicals, so-called xenoestrogens, has been used to suggest that risks arising from exposure to individual chemicals are negligible. Another argument used to dismiss concerns of health effects is that endogenous steroidal estrogens are too potent for xenoestrogens to contribute significantly to estrogenic effects. Using a yeast reporter gene assay with the human estrogen receptoralpha, we tested these ideas experimentally by assessing the ability of a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
234
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(247 citation statements)
references
References 32 publications
10
234
0
3
Order By: Relevance
“…Certain evidence has indicated that adverse effects of mixtures could be induced from exposure to many compounds at or below NOEC Rajapakse et al, 2002;Ge et al, 2011). We assessed the joint effects of the eleven and nine individual PFAAs at IC 0 concentration corresponding to a true zero effective concentration in our test system.…”
Section: Non-monotonic Concentration-response Relationships Of Multipmentioning
confidence: 99%
“…Certain evidence has indicated that adverse effects of mixtures could be induced from exposure to many compounds at or below NOEC Rajapakse et al, 2002;Ge et al, 2011). We assessed the joint effects of the eleven and nine individual PFAAs at IC 0 concentration corresponding to a true zero effective concentration in our test system.…”
Section: Non-monotonic Concentration-response Relationships Of Multipmentioning
confidence: 99%
“…A cumulative risk approach goes beyond identifying effects of individual endocrine disruptors by considering the possibly additive, antagonistic, or synergistic activity of simultaneous exposures to many agents that may affect children's health (Rajapakse et al 2002). Future cumulative risk assessments will consider a) how exposures to multiple agents alter the toxicity of endocrine disruptors, b) how genes, life stages, lifestyles, and diseases can affect the toxicity of endocrine disruptors, and c) how exposure to endocrine disruptors can alter the toxicity of other agents.…”
Section: Exposure Assessment In Hypothesis Testing and In Hypothesis mentioning
confidence: 99%
“…Partial agonists only partially fulfill this requirement and thus cause the mixture curves to deviate from that of E2 at higher concentrations. The difficulty of predicting maximum effect levels of mixtures containing partial agonists with the CA model is also discussed by others (3,11). In our experiments, MILs of mixtures containing partial agonists could, however, roughly be estimated by calculation of the average MIL of the mixture components, weighted by their relative contributions to the total estrogenic activity of the mixture (last column in Table 2).…”
Section: Resultsmentioning
confidence: 63%
“…The contribution of each component to the total effect of the mixture is considered to be proportional to its estrogenic potency and its concentration in the mixture. The CA concept has previously been shown to be valid for the prediction of mixture effects of estrogenic compounds in the yeast estrogen screen (YES assay) (3,11,12). Like the YES assay, the ER-CALUX assay is based on a receptor gene construct, with activation of the endogenous estrogen receptors as the sole molecular mechanism leading to response.…”
Section: Introductionmentioning
confidence: 99%